ANALISIS KOMPARASI IMBAL HASIL SAHAM-SAHAM UNDER VALUE TERHADAP INDEK HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA - Sunarso Sunarso (Jurnal Manajemen Kewirausahaan, 2017)
There are many form of investment instruments in the capital market. One of them is to buy stock in the capital market.  Invesment in the capital market by buying  a set of stocks  is called portfolio investment. To get optimum return in the portfolio investment, an effective strategy must be implemented. By implementing the strategy investor can manage risk to avoid excessive loss in their investment. One way to achieve the goal is to buy under value stocks. Under value stocks price commonly discount below their book value and their price earning ratio (PER) below average. The  discount is an opportunity to gain big profit for long time investors. In the long term, investing on these stocks will give higher return with lower risk. This investment can be said as high return and low risk strategy. This strategy is suitable  in managing risks for retail investors in the Indonesian Capital Market (BEI), especially for long term retail investor. The real investors realize that investment is a sacrifice of today consumtion to to rise capital gain in the future.This research is aimed to  compare risk and return among under value stocks with composite index as well as sectoral index in the Indonesian Stock Market (BEI).  The methood in this research is descriptive reseach. The raw data taken from monthly transaction of  undervalue stocks and composite index as well as sectoral index from March 2016 to December 2016. At the beginning of the periode each stock  that its price below book value but its PER under  average of the least five of sectoral PER, is taken for the research objects. At the end period, the return or the loss of the stock was calculated and compared with composite and sectoral return. The result of the calculation was presented  on the data analysis.  Base on this research we found that the risk of under value stocks are lower and the profit are higer than composite index as well as sectoral index. Kata Kunci: Under Saham Nilai, Risiko dan Return, Instrumen